Choice of radiotherapy modality for the combined treatment of non-small cell lung cancer with brain metastases: whole-brain radiation therapy with simultaneous integrated boost or stereotactic radiosurgery - Dong, Xiaotao; Wang, Kunlun; Yang, Hui; Li, Yan; Hou, Yanqi; Chang, Jiali; Yuan, Ling (Frontiers in Oncology, 2023)
Contribution to the field The optimal treatment for brain metastasis (BM) has not been determined, and the survival benefit of surgical resection in selected patients remains controversial. Radiotherapy and drug therapy are the mainstream treatments for BMs. Previous studies mainly focused on chemotherapy combined with radiotherapy (usually Whole-Brain Radiation Therapy (WBRT)). Immunotherapy and targeted therapy have recently become increasingly popular in systemic drug therapy for BM patients. Which means previous studies on radiation therapy for non-small cell lung cancer with BM have drug limitations. The topic of our study is which radiotherapy modalities(WBRT with Simultaneous Integrated Boost (WBRT+SIB)or Stereotactic Radiosurgery(SRS)) have survival benefits in combination with systemic drugs. In addition, survival related factors of NSCLC patients with brain metastases were found, We conducted a single-centre retrospective study and concluded that WBRT+SIB may have better intracranial control and exemplary safety, establishing the best strategies for treating non-small cell lung cancer with brain metastases.